Review: Perspective of Biotic and Abiotic Factors for Tropical Orchid Acclimatization and Ex-situ Conservation - Kinasih, Anggiresti; Rafli, Muhamad; Nugrahening, Eria Rosanti; Hidayah, Nurul; Oktaweni, Fiola; Budiastuti, Novi Saptariani (Jurnal Biologi Tropis, 2025)
Acclimatization represents a critical transition phase in ex-situ conservation of tropical orchids, marking the shift from sterile in vitro conditions to more variable external environments. This literature review aims to synthesize recent experimental findings on the influence of abiotic and biotic factors on seedling viability and to propose an effective acclimatization protocol. A systematic analysis was conducted on over 30 peer-reviewed articles published between 2014 and 2024, covering media formulation, substrate selection, environmental controls, and microbial inoculation. The results highlight that optimized substrates such as moss, coconut fiber, and carbonized rice husk significantly improve root aeration and water retention. Supplementation with organic additives (e.g., peptone, coconut water, banana pulp) enhances early seedling vigor when applied to modified Murashige and Skoog (MS) media. Environmental parameters especially light intensity, diurnal temperature fluctuation (DIF), humidity, and photoperiod directly affect physiological responses. Moreover, inoculation with plant growth-promoting bacteria (PGPB) and mycorrhizal fungi contributes to phosphate solubilization, nitrogen fixation, siderophore production, and stress tolerance. In conclusion, the integration of species-specific abiotic and biotic strategies enhances survival and growth, offering scalable potential for orchid conservation and commercial propagation. It is recommended that future research focus on long-term physiological assessments and standardized inoculant formulations to improve protocol consistency across diverse orchid taxa.